Amides derived from heteroaromatic amines and selected steryl hemiesters - Bildziukevich, Uladzimir; Rárová, Lucie; Saman, David; Havlíček, Libor; Drašar, Pavel; Wimmer, Zdeněk (Steroids, 2013)
The current interest of the team has been focused on investigation of novel amides with potential cytotoxicity. The presented series of compounds was synthesized from selected steryl hemiesters and heteroaromatic amines. The synthetic protocol was designed in a simple and economic way, and divided into several general methodologies applicable to the compounds synthesized. The cytotoxicity was tested on cells derived from human T-lymphoblastic leukemia, breast adenocarcinoma and cervical cancer, and compared with tests on normal human fibroblasts. Most of the lanosterol-based compounds (3-5 and 7-10) showed medium to good cytotoxicity, while only two derivatives of cholesterol (18 and 19) showed medium cytotoxicity on human T-lymphoblastic leukemia cell line. The compounds 8 and 9 displayed the reasonable cytotoxicity among this series of amides, tested on the cell lines of T-lymphoblastic leukemia [14.5±0.4 μM (8) and 18.5±3.9 μM (9)], breast adenocarcinoma [19.5±2.1 μM (8) and 23.1±4.0 μM (9)] and cervical cancer [24.8±5.3 μM (8) and 29.1±4.7 μM (9)]. Only the compound 8 was adequately less active on normal human fibroblasts (40.4±11.1 μM).
Keywords: nádorové buněčné linie; Lanosterol; HeLa; Drug Screening Assays, Antitumor; Dulbecco’s modified Eagle’s medium; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; DMEM; Cytotoxins; screeningové testy protinádorových léčiv; lanosterol; aminy; 50% solution of propylphosphonic anhydride in ethyl acetate; MCF7; Cell Proliferation; Cell Line, Tumor; Antineoplastic Agents; Cholesterol; Amide; cells of human T-lymphoblastic leukemia; N,N′-dicyclohexylcarbodiimide; normal human fibroblasts; CEM; protinádorové látky; amidy; Humans; DMAP; 4-(N,N-dimethylamino)pyridine; FBS; Amines; viabilita buněk; Cell Survival; Fibroblasts; 9H-fluoren-9-ylmethyl carbonochloridate; T3P; cells of human breast adenocarcinoma; cells of human cervical cancer; proliferace buněk; fibroblasty; Amides; foetal bovine serum; Cytotoxic activity; DCC; FMOC-Cl; cytotoxiny; BJ; Heteroaromatic amine; lidé; cholesterol